Mouse tales - Lobel, Arnold ([New York] : HarperCollins, 1972)
In order to get his seven little mouse children to sleep, Papa Mouse tells seven individual bedtime stories.
"Reading with help, 2"--Cover.
Booklist.
School Library Journal.
Wilson's Children.
2.6.
2.6
Keywords: Mice -- Fiction; Mice -- Fiction; Readers (Elementary).